THE INFLUENCE OF AUTHORITARIAN LEADERSHIP STYLE AND WORK ENVIRONMENT ON THE ORGANIZATIONAL COMMITMENT OF MAKASSAR CLASS 1 PRIVATE EMPLOYEES - Fresiska; Hety Budiyanti; Tenri Sayu Puspitaningsih Dipoatmodjo; M. Ilham Wardhana Haeruddin; Rezky Amalia Hamka (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
This research aims to determine the influence of authoritarian leadership style and the work environment on the organizational commitment of employees at the Makassar Class 1 Detention Center. This research uses a quantitative type of research using a descriptive approach method. The population in this study was 175 employees and the sample used was 120 respondents. Data collection was carried out using questionnaires, observation, interviews and documentation methods. The data analysis technique used is multiple linear regression analysis using statistical product and service (SPSS) 25. The results of the research show that the authoritarian leadership style has an insignificant influence on the organizational commitment of employees at the Makassar Class 1 Detention Center with a value of 0.450 > 0.050 and a calculated t value of -.758 < t table of 2.358. The work environment has a significant influence on the organizational commitment of employees at the Makassar Class 1 Detention Center with a value of 0.000 < 0.050 and a calculated t value of 6.129 > t table of 2.358. The authoritarian leadership style and work environment both have a significant influence on the organizational commitment of employees at the Makassar Class 1 Detention Center with a calculated F value of 26.983 > F table of 3.16 or a sig of 0.000 < 0.050.